INOVASI PENGEMBANGAN NILAI-NILAI AGAMA PADA ANAK USIA DINI - Nurfaizah; Mhd.Habibu Rahman (QURROTI, 2020)
The development of religious values ​​in early childhood is very important so that students have and understand good religious values, so that in living life, children better understand the values ​​of the religious teachings they adhere to and when students enter the next level they already have the knowledge , and good experience. The purpose of this research is to find out what innovations are needed in the development of religious values ​​in early childhood. This research was studied using descriptive methods and a library research approach as a place or source of reference. The results of the study show that the forms of early childhood diversity include Unreflective, Egocentric, Anthromorphic, Verbalist and Ritualist, and Imitative. The innovations made in developing AUD's religious values ​​are through experiential learning, active learning and process learning. The principles of innovation for the development of AUD's religious values ​​are the principles of developmentally appropriate practice (DAP), the principle of enjoyable. One of the learning models that can be used in developing early childhood religious values ​​is the quantum learning model. While the methods for developing children's religious values ​​are playing, field trips, telling stories.